Adapted physical educators' beliefs and intentions for promoting out of school physical activity - Pawlowski, Jill; Yun, Joonkoo (European Journal of Adapted Physical Activity, 2019)
The purpose of this study was to examine beliefs, intentions, and behaviors of promoting out-of-school physical activity among adapted physical education teachers and comparing these beliefs, intentions, and behaviors with those of general physical education teachers. A total 253 physical educators including 208 general physical education and 45 adapted physical education teachers completed the survey measuring their behavior, attitude, self-efficacy, social normative beliefs, intention, and implementation intention of out-of-school physical activity promotion. Multiple linear regression analysis revealed significantly lower out-of-school physical activity promotion self-efficacy among adapted physical education teachers (β = .66; BCI = .18, 1.13) than general physical education teachers with no difference in other outcome variables between groups. This finding could be due to a lack of training on out-of-school physical activity promotion in teacher preparation programs and institutional limitations on adapted physical education.
Keywords: Children; Disabilities; Sedentary behavior